Early vs Late Coronary Angiography and Intervention Following Thrombolytic Therapy; a Cohort Study - Feizi, Bahareh; Taghdisi, Shahram; Etemadi, Jalil; Feizi, Amir Hossein; Asgarzadeh, Setareh; Kamal, Sepideh (Archives of Academic Emergency Medicine, 2017)
Introduction: The precise time of using percutaneous coronary intervention (PCI) after fibrinolytic therapy for maximum efficiency and minimum side effects is still undetermined. Therefore, the present study was designed to compare the outcome of myocardial infarction (MI) patients who underwent surgical intervention (angiography and PCI) within 48 hours of thrombolytic therapy or after that. Methods: The present study is a prospective cohort study aiming to compare the occurrence of no-reflow phenomenon, unstable angina, bleeding during intervention, and one month major adverse cardiac outcomes (recurrent MI, need for repeating surgical intervention, and mortality) between MI patents undergoing surgical intervention within the first 48 hours of or after 48 hours of thrombolytic therapy. Results: 90 patients with the mean age of 54.97 ± 10.54 were studied (86.67% male). 50 (56%) patients underwent surgical intervention within 48 hours and 40 (44%) after that. The 2 groups were not significantly different regarding baseline characteristics. No-reflow phenomenon in the < 48 hours group was about twice the > 48 hours group (OR = 0.35; 95% confidence interval: 0.14 – 0.92; p = 0.03), other outcomes were not significantly different. No case of mortality was seen in the 1 month follow up. Conclusion: Based on the results of the present study, it seems that no-reflow phenomenon rate is significantly lower in patients undergoing surgical intervention after 48 hours of fibrinolytic therapy. The difference between the two groups regarding prevalence of major adverse cardiac outcomes was not statistically significant.